Bromine isotope effects: Predictions and measurements. (May 2020) - Gelman, Faina; Dybala-Defratyka, Agnieszka
Abstract: Brominated organic compounds (BOCs), abundant in Nature, originate from its own sources or anthropogenic activity. Many of these compounds are harmful and constitute a serious threat, therefore it is important to study and understand their behavior and fate. In situ, BOCs undergo various chemical and biochemical reactions through distinctive mechanistic pathways. However, breaking C–Br specific bond is a crucial step in the transformation of brominated organic compounds. Understanding the mechanisms of debromination can be substantially enhanced by studying Br isotope effects. In this Mini-review we provide overlook of existing experimental techniques for Br isotope analysis, discuss Br kinetic isotope effects measured for selected chemical and biochemical reactions in the light of underlying reaction mechanisms, and review the outcome from computational study of performed to provide more insightful interpretation of observed findings. Graphical abstract: Image 10908 Highlights: Br isotope effects are crucial in describing brominated organics fate in the environment. Modern analytical methods allow for precise measurement of bromine isotopic ratios. Combined the experimental and theoretical approaches to determine Br IEs are discussed.